PERANCANGAN SISTEM PENDETEKSI DAN PENANGGULANGAN BANJIR MENGGUNAKAN ESP32 BERBASIS IOT - Yuslan Basir; M.Rizki Adi Pratama; Moh. Wahyu Aminullah (Universitas Nasional, 2023)
The design of a flood detection and prevention system using an IoT-based esp32 which functions to unify the water level and can be controlled via a smartphone with the blynk application, this tool is designed using the esp32 controller as a wifi module, the water level sensor is a marker of the water discharge level and the relay works as a switch. The way this tool works is to detect the arrival of flooding through a level sensor and the data is directed to the esp32 microcontroller as a medium and sent through the output of the light indicator, LCD display and smartphone, a blynk application called flood monitoring is applied, if the water touches the level 3 sensor it turns on and sends notification to the red light indicator. LCD display and the blynk application, the flood detection and control system can work well after being tested for flood monitoring and control through the blynk application.